THE INFLUENCE OF TIRE RUBBER PULLING EXERCISE MEDIA ON ARM MUSCLE STRENGTH IN VOLLEYBALL ATHLETES OF PUTRA RAMAS TABANAN CLUB - Dei, Agustinus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
The purpose of this study was to determine the effect of rubber tire pulling training media on arm muscle strength and to determine the differences in the results of tire rubber pulling training with smash training without using a ball. This study used an experimental randomized pre-test and post-test groups design. The population was taken from all athletes at the Putra Ramas volleyball club in 2021. The data are the results of arm muscle strength when pulling the expanding dynamometer taken before and after training. The obtained data were tested using the SPSS 22 computer program. The data were normally distributed and homogeneous, so that they were then tested using paired t-test to compare the average values ​​before and after training between each group, while the independent t-test was to determine the difference in the average values ​​between the two groups. The conclusion is that pulling the rubber tire with 10 repetitions of 3 sets and smash training without using the ball for 10 repetitions of 3 sets both increase arm muscle strength and states that the alternative hypothesis is accepted.